Ghosts of Girlfriends Past - Waters, Mark S., 1964-; Shestack, Jonathan; Epstein, Brad; Lucas, Jon; Moore, Scott; McConaughey, Matthew, 1969-; Garner, Jennifer, 1973-; Douglas, Michael, 1944-; Archer, Anne; Meyer, Breckin, 1974-; Chabert, Lacey, 1982-; Forster, Robert; et al. ([Burbank, CA] : New Line Cinema, 2009)
A committed bachelor who thinks nothing of breaking up with several women on a conference call is visited by the ghosts of his former jilted girlfriends, who take him on a hilarious adventure through his failed relationships - past, present, and future.
DVD, region 1; Dolby Digital 5.1 surround sound.
Originally released as a motion picture in 2009.
Dual-layer format ; standard ed.
Music by Rolfe Kent ; editor Bruce Green ; director of photography, Daryn Okada.
Michael Douglas, Breckin Meyer, Anne Archer, Matthew McConaughey, Lacey Chabert, Jennifer Garner, Robert Forster, Emma Stone.
MPAA rating: PG-13, some material may be inappropriate for children under 13, for sexual content throughout, some language and a drug reference.
Keywords: Bachelors -- United States -- Drama; Men -- Sexual behavior -- Drama; Ghosts -- United States -- Drama; Weddings -- United States -- Drama; Brothers -- United States -- Drama; Man-woman relationships -- United States -- Drama; Video (DVD); Feature films; Films for the hearing impaired; Comedy films; Romantic comedy films